VITALISASI SISTEM EKONOMI ISLAM MENUJU KEMANDIRIAN PEREKONOMIAN UMAT - Syaparuddin Syaparuddin (AL-IQTISHAD, 2020)
AbstractThe Islamic ecomic system in the specifik characteristics, is very different from the other economic system because it is as an integral part of islamic system, and economic in islam brings an equilibrium for individual and public interest, as well as it brings an individual freedom for economic activities. In the effort of completing its acknowledgment to economic freedom, Islam gives an authory to the government to interfere in the fungsionalization of islamic ecomic system. It means that all matters which concern on the economic aspects, have been discussed in Islam. So that it could be concluded that the regulation of economic in Islam, is absolutely complete. Therefore, the application of Islamic economic system in the social order of community’s economy would bring prosperity and benefit for community it self.Kata Kunci: Islam; Ekonomi; Sistem; Umat.